Purification and transcriptomic characterization of proliferative cells of Mesocestoides corti selectively affected by irradiation - Costábile, Alicia; Domínguez, María Fernanda; Guarnaschelli, Inés; Preza, Matías; Koziol, Uriel; Castillo, Estela; Tort, José F. (Frontiers in Parasitology, 2024)
Flatworms depend on stem cells for continued tissue growth and renewal during their life cycles, making these cells valuable drug targets. While neoblasts are extensively characterized in the free-living planarian Schmidtea mediterranea, and similar stem cells have been characterized in the trematode Schistosoma mansoni, their identification and characterization in cestodes is just emerging. Since stem cells are generally affected by irradiation, in this work we used this experimental approach to study the stem cells of the model cestode Mesocestoides corti. We found that gamma irradiation produces a dose-dependent decrease in proliferative cells, requiring higher doses than in other flatworms to completely abolish proliferation. The treatment results in the downregulation of candidate marker genes. Transcriptomic studies reveal that several genes downregulated after irradiation are conserved with other flatworms, and are related to cell cycle, DNA replication and repair functions. Furthermore, proliferative cells were isolated by cell sorting and also characterized transcriptomically. We found that the set of genes characteristic of proliferative cells agrees well with those downregulated during irradiation, and have a significant overlap with those expressed in planarian neoblasts or S. mansoni stem cells. Our study highlights that conserved mechanisms of stem cell biology may be functional in flatworms, suggesting that these could be relevant targets to evaluate in the control of parasitic species.